Influence of the HACCP system on the continuous improvement of the line of ready meals in a selfservice store of Lima Metropolitan area (Peru) - Rosas Aparicio, Gilda (2018)
This research aims to determine how the quality management, based on the HACCP system (Hazard Analysis and Critical Control Points), influences on the continuous improvement of the Line of Ready Meals in a self-service store of Lima Metropolitan Area to 2015. For this reason, the continuous improvement was studied from two perspectives: Responsibility of food handling personnel and the conditions of process and manufacturing and sanitary facilities. The type of research was pre-experimental; the sample of study was conformed by 16 people who work in the Line of Ready Meals of a self-service store of Lima Metropolitan Area. It is concluded that the HACCP system has had a significant influence on continuous improvement, as well as, on the responsibility of food handlers and the conditions of processing and manufacturing and sanitary facilities of self-service store.